Tinjauan Waktu Pelaksanaan Pondasi Tapak Sumuran Pada Ruang Kelas Baru (RKB) SMP-UQ (Ulumul Qur’an) Kabupaten Pidie - Dedek Ariansyah, (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2022)
Planning and controlling costs and time are part of construction project management. Therefore, realistic planning is needed as a benchmark and control method that can continuously monitor deviations from costs that have been incurred and time spent in completing construction projects. Therefore, it is necessary to review the extent to which the minimum execution time of work by using manpower and equipment is in accordance with the volume of work. The purpose of this study was to plan the time for the implementation of the foundation work for the New Classroom (RKB) of SMP-UQ (ULUMUL QUR'AN) Pidie Regency, which is located on Jln. Tijue - Cot Teungoh Madrasah Ulumul Qur'an Pidie Complex. The construction being reviewed is the RKB which includes time schedule, use of labor and equipment that supports work productivity. The research method is based on the CPM (Critical Path Method). The results showed that all works were on the critical path except for the construction of footings and poor piles. The number of days obtained in planning the time of foundation implementation is 34 days with effective working hours in 1 day is 7 hours.